Analisis Penerapan Nilai Karakter Disiplin Melalui Kegiatan Ekstrakurikuler Drumband - Rohmah, Nur Hanifatul; Pusari, Ratna Wahyu; Purwadi; Hariyanti, Dwi Prasetiyawati Diyah; Munawar, Muniroh; Luthfy, Perdana Afif (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Through the character of discipline, children can learn the rules that exist in the family, school, and community environments. This study aims to analyze the application of the character value of discipline through the extracurricular activity of drum band at Semesta 3 Kindergarten B in Semarang. Data were collected through observation, interviews, and documentation. The observation was carried out on 8 children, directly by observing the children's disciplined character through interactions between the teacher, the children and the trainer. Interviews were conducted with 1 drum band trainer and 4 classroom teachers. Interviews were conducted to find out how teachers discipline children. Documentation was carried out with notes, photos and videos. Data analysis used Miles and Huberman's data analysis techniques, namely data collection, data reduction, data display and conclusion drawing/verification. Triangulation of sources, techniques and time is used to verify the accuracy of the information. From the results of the study, the application of the character value of discipline through extracurricular activities such as drum bands was obtained, (1) Teachers make children get used to being on time, (2) Teachers make children get used to tidying up, (3) Teachers make children get used to lining up in front of the class, (4) Teachers make children take turns when taking drums, (5) The coach makes the children get used to performing drum band movements simultaneously or in unison, (6) The teacher makes the children get used to listening to directions. The researchers' advice is directed at schools to keep innovating and emphasizing character values in every extracurricular activity at school.